Prevalence and antimicrobial susceptibility of Vibrio species related to food safety isolated from shrimp cultured at inland ponds in Thailand - Yano, Yutaka; Hamano, Kaoru; Satomi, Masataka; Tsutsui, Isao; Ban, Masatoshi; Aue-umneoy, Dusit (My University, 2014)
Inland farming of marine shrimp species is a relatively recent development, in response to increasing demand for the products. This study aimed to investigate the prevalence and antimicrobial resistance ofpotentially pathogenic Vibrio species in shrimps cultured at inland ponds with low salinity in Thailand. Of 16 shrimp samples (white-leg shrimps and black-tiger shrimps) from ponds with water temperatures from 29 to 32°C, and salinities from 1 to 5 parts per trillion, 15 contained Vibrio cholerae (densities: 62-252,000MPN/g). Vibrio parahaemolyticus was present in six samples (370-6,300,000MPN/g), and Vibrio vulnificus was present in two samples (16-1300MPN/g). V.parahaemolyticus has higher affinity for non-native white-leg shrimp than for native black-tiger shrimp. The minimum inhibitory concentrations were then measured for 12 common antimicrobial agents. Resistance to ampicillin and oxytetracycline (8% and 2% of the isolates) was documented in V.cholerae isolates, resistance to ampicillin and oxytetracycline (72% and 3%) was found in V.parahaemolyticus isolates, and resistance to nalidixic acid (20%) was detected in V.vulnificus isolates. β-lactamase and tetracycline resistance genes were detected in the resistant Vibrio isolates. The oxytetracycline-resistance phenotype was eliminated by plasmid curing, suggesting that the resistance was related to R-plasmids. Our results show that shrimps cultured even in low salinity ponds are potentially contaminated with pathogenic Vibrio species, and that shrimp are a vehicle for transfer of species with antimicrobial resistance genes to the public. © 2013 Elsevier Ltd.
Keywords: Antimicrobial resistance; Shrimp; Thailand; Vibrio cholerae; Vibrio parahaemolyticus; Vibrio vulnificus